Analisis Standar Operasional Prosedur pada Rintisan Teaching Factory Tax Corner Politeknik Negeri Jember - rahma rina wijayanti; Oryza Ardhiarisca; Zilvanhisna Emka Fitri; Datik Lestari; Cherry Triwidiarto; Supriyadi Supriyadi (Universitas Negeri Surabaya, 2023)
This study aims to develop a standard operating procedure (SOP) for the Teaching Factory (TEFA) Tax Corner at the Jember State Polytechnic (Polije). This is one of the preparations for the establishment of the TEFA Tax Corner. This research is a qualitative research. The data used in this study are primary and secondary data. Primary data obtained from interviews with resource persons, field observations, data analysis. Secondary data is obtained from data supporting the TEFA Tax Corner business process. The first step of this research is to identify the activities at TEFA Tax Corner by visiting the Tax Center FISIP, University of Jember (UNEJ). During the visit, observations, interviews and documentation were carried out on the activities carried out at the UNEJ Tax Center. Furthermore, planning activities to be carried out at Polije, namely tax webinar, webinar related to tax research, training in filling out tax forms, making Management Decrees, cash receipts and cash disbursements. The next stage is making SOPs for these activities by taking into account the bureaucratic conditions in Polije. Classification of the parties and documents related to the TEFA activities and the flow or steps of these activities are carried out. The output of this research is SOP webinars and training, making Management Decrees, cash receipts and cash disbursements.